A Rare Case of Delayed Perigastric Abscess after Curative Resection of Early Gastric Cancer by Uncomplicated Endoscopic Submucosal Dissection: Successful Treatment with Endoscopic Ultrasound-guided Drainage - Asayama, Naoki (Intern Med, 2020)
A 72-year-old man had undergone uncomplicated endoscopic submucosal dissection (ESD) with en bloc resection of a localized 20-mm IIc lesion in the anterior wall of the gastric angle. Twenty-eight days later, he was re-admitted with epigastric pain of one-week duration. Contrast-enhanced computed tomography (CT) revealed a 60-mm mass bordered by viscera; repeat endoscopy confirmed a smooth elevated submucosal tumor at the greater curvature on the oral side of the post-ESD ulcer. We diagnosed him with a perigastric abscess as a complication of ESD and performed endoscopic ultrasound-guided drainage. Subsequently, the symptoms and blood inflammatory parameters improved, and follow-up CT showed the disappearance of the abscess.